Our natural "makeup" reveals more than it hides: Modeling the skin and its microbiome. Issue 1 (15th June 2020) - Hussan, Jagir R.; Hunter, Peter J.
Abstract: Skin is our primary interface with the environment. A structurally and functionally complex organ that hosts a dynamic ecosystem of microbes, and synthesizes many compounds that affect our well‐being and psychosocial interactions. It is a natural platform of signal exchange between internal organs, skin resident microbes, and the environment. These interactions have gained a great deal of attention due to the increased prevalence of atopic diseases, and the co‐occurrence of multiple allergic diseases related to allergic sensitization in early life. Despite significant advances in experimentally characterizing the skin, its microbial ecology, and disease phenotypes, high‐levels of variability in these characteristics even for the same clinical phenotype are observed. Addressing this variability and resolving the relevant biological processes requires a systems approach. This review presents some of our current understanding of the skin, skin–immune, skin–neuroendocrine, skin–microbiome interactions, and computer‐based modeling approaches to simulate this ecosystem in the context of health and disease. The review highlights the need for a systems‐based understanding of this sophisticated ecosystem. This article is categorized under: Infectious Diseases > Computational Models Abstract : The skin microbiome is strongly coupled with the skin resident immune and neuroendocrine systems, which in turn are coupled with their systemic counterparts. These systems together modulate the skin physiology. Pointed arrows indicate activation, blunt‐end arrows indicate inhibition.